Dampak Pemecatan Sewenang-Wenang Hakim Konstitusi Terhadap Masa Depan Konstitusi Nasional Indonesia: Kesewenangan, Mahkamah Konstitusi, Hakim - Sabila Riri (Jurnal Penelitian Multidisiplin, 2023)
At present, constitutional institutions have efforts to be politicized by the exact same institution, namely the legislative body. According to Kurnia Ramadhana, ICW's Political Corruption Division, in a seminar organized by Sahabat ICW, there was a haphazard and authoritarian practice of the DPR RI towards the Constitutional Court which was very clearly seen, both from the actions after the plenary session of the DPR RI and from the statements of DPR members. Qualitative method . In this case, it can be said that what was done by the DPR was contrary to the 1945 Constitution which should not have been carried out because it was contrary to the principle of constitutional supremacy. What was done by the DPR considered attacking the independence of power at the heart of the country, namely the Constitutional Court by legal experts, one of whom was Palguna I Dewa Gede, a former constitutional judge According to legal experts and former constitutional judges, that the Constitutional Court is an institution that is considered the heart of the country, constitutional supremacy that must stand upright. If an independent constitution is intervened by another power institution, it will have an impact on the supremacy of the constitution itself. This also causes constitutional institutions to lose their independence, and what is done by the DPR is considered contrary to the 1945 Constitution. This will have an impact on the supremacy of the constitution itself. This also causes constitutional institutions to lose their independence, and what is done by the DPR is considered contrary to the 1945 Constitution. This will have an impact on the supremacy of the constitution itself. This also makes constitutional institutions lose their independence, and what is done by the DPR is considered contrary to the 1945 Constitution.